Towards an efficient SEU effects emulation on SRAM-based FPGAs. (November 2016) - Souari, Anis; Thibeault, Claude; Blaquière, Yves; Velazco, Raoul
Abstract: A novel fault injection approach, reproducing results obtained from radiation ground testing while studying the Single Event Upset (SEU) effects on SRAM-based Field Programmable Gate Arrays (FPGAs), is presented. This approach can take into account the relative sensitivity difference between configuration bits set to '0' and those set to '1'. According to irradiation experiments conducted under proton beam for a Xilinx Virtex-5 FPGA at the TRIUMF lab, configuration bits set to '1' are approximately twice as sensitive as bits set to '0'. This fact was exploited in test sequence generation while performing fault injection experiments, in order to generate more realistic emulation results. The effectiveness of the approach is validated by comparing its results to those obtained with proton radiation tests, for two different ring-oscillator-based experimental setups. It shows that taking this sensitivity into account helps obtain more realistic results while dealing with delays induced by radiation, which justifies considering this relative sensitivity during fault emulation. In fact, comparing the results obtained from the proposed approach to those obtained at TRIUMF gives an absolute relative error of 3.1 and 14%, respectively, for the first and the second setups, while estimating the error between the latter and results from a conventional random fault injection provides error values of up to 75%. Finally, applying our fault injection approach on a more conventional circuit reveals that taking the relative sensitivity difference into account leads to 2.3 times as many errors detected as with random injection. This last result suggests that not taking the relative sensitivity difference into account during emulation can lead to an underestimation of a design sensitivity to radiation. Highlights: Considering the sensitivity asymmetry of configuration bits in fault injection Generating more realistic results, closer to those from radiation proton test Enhancing reliability evaluation compared with random emulation